2015
DOI: 10.1080/02640414.2015.1064156
|View full text |Cite
|
Sign up to set email alerts
|

The colour of a football outfit affects visibility and team success

Abstract: We investigated the impact of the colour of football outfits on localising football players and on the results of football matches. Two studies were conducted: an experimental study examining the effects of outfit colour on the assessment of the positions of computer-animated football players in a video set-up (study 1) and a retrospective study on professional football clubs' performances dependent on their outfit colours (study 2). The studies were conducted with 18 human volunteers aged 15-18 years (study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
4
15
0
1
Order By: Relevance
“…Research on color biases in winning may contribute to improving fairness in sport and equal opportunities for each athlete, regardless of their uniform color. For example, previous studies have stated that “smart use of color may improve team results” (Olde Rikkert et al, 2015 ). Our findings may have important implications for (combat) sports policy makers; as our results suggest, a blue–white pairing ensures an equal level of play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on color biases in winning may contribute to improving fairness in sport and equal opportunities for each athlete, regardless of their uniform color. For example, previous studies have stated that “smart use of color may improve team results” (Olde Rikkert et al, 2015 ). Our findings may have important implications for (combat) sports policy makers; as our results suggest, a blue–white pairing ensures an equal level of play.…”
Section: Discussionmentioning
confidence: 99%
“…The white judogi was suggested to be more visible than the blue judogi , allowing the athlete in blue to better evaluate and anticipate the movement of his (white) opponent. While perceptual differences in moving objects of a certain color may indeed influence localizing team players and potentially the likelihood of winning in for example football matches (Olde Rikkert et al, 2015 ), differential perception effects are unlikely to occur in situations where athletes are directly fighting an opponent in close quarters. A second explanation was given by Barton and Hill ( 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the green lawn of a football pitch, players wearing green possess a lower color contrast resulting in a lower visibility. [38][39][40][41][42] Thus, the players might be more difficult to detect on a similar-colored background, as already suggested by Rowe et al 36 However, experimental research has already emphasized the significance of color brightness for color detection and appearance on chromatic backgrounds. [39][40][41][42][43] Considering a lower detection rate and speed for darker colors (minor values of lightness), black kits were also expected to carry an advantage for attacking and defending teams on offside judgments because of the increased complexity of their perceptual detectability.…”
Section: Discussionmentioning
confidence: 91%
“…Even when Rowe et al 36 results and assumptions were disputed controversially, 33,37 Olde Rikkert et al transferred their assumption to association football showing that the color of football outfit affected evaluations of players' positions on the field. 38 They showed that the positions of virtual players wearing green proved significantly less assessable for participants than the positions of players wearing white in a green football field environment. Color research clearly pointed out that a high colour contrast facilitates the detection rate and detection speed of a target stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation